The Evaluation of Virtual Reality Fire Extinguisher Training - Saghafian, Mina; Laumann, Karin; Akhtar, Ragheeba Sadaf; Skogstad, Martin Rasmussen (Frontiers in Psychology, 2020)
The aim of this research was to explore trainees’ perceptions and evaluation of Virtual Reality fire extinguisher training. Virtual Reality technology is being adopted by many industries for various purposes including safety training for safety critical industries. The future direction of Virtual Reality training requires an understanding of trainees’ evaluation of it; this fact motivated this research. Data were collected from 85 participants using a questionnaire after the training. Observation notes were taken to provide a better understanding of the context. Qualitative research with a thematic analysis was used to analyze the data. The results of this analysis revealed that the most salient themes reflect on issues surrounding the realism of the Virtual Reality simulation, namely different emotional and bodily experiences during the training, while the benefits of the training (health, safety, environmental advantages, efficiency and convenience, repeatability and variety of scenarios) make it a good supplement. Nevertheless, improved realism is needed to make it more effective and enhance transfer and acceptance. This study encourages the consideration of important matters (such as realism and emotions) when using Virtual Reality for fire training. It also describes the positive perceptions of this type of training (repeatability of training, safety and environmental concerns).